Alkylation of m-Cresol with Cyclopentene in the Presence of p-Toluenesulphonic Acid (Bangladesh Journal of Scientific and Industrial Research, 2008)
m-Cresol has been cycloalkylated with cyclopentene in the presence of p-toluenesulphonic acid as catalyst. The effects of the variation of temperature, molar ratio of m-cresol to cyclopentene, time of reaction and amount of catalyst have been investigated on the reaction and cyclopentyl m-cresol has been obtained in high yield. Key words: Alkylation , m-Cresol, time frechtion, molar ration Bangladesh J. Sci. Ind. Res. 42(4), 499-502, 2007